2020
DOI: 10.1093/gerona/glaa018
|View full text |Cite|
|
Sign up to set email alerts
|

Patients’ and Caregivers’ Attitudes Toward Deprescribing in Singapore

Abstract: Background Knowledge of decision-making preference of patients and caregivers is needed to facilitate deprescribing. This study aimed to assess the perspectives of caregivers and older adults towards deprescribing in an Asian population. Secondary objectives were to identify and compare characteristics associated with these attitudes and beliefs. Method A cross-sectional survey of two groups of participants was conducted usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 37 publications
3
35
1
Order By: Relevance
“…Our finding that most participants (89%) would be willing to stop one of their regular medications on their physician's advice is in accordance with previous literature 8‐12,21‐23 . Interestingly, only one third reported an intrinsic desire to try stopping one of their medications.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding that most participants (89%) would be willing to stop one of their regular medications on their physician's advice is in accordance with previous literature 8‐12,21‐23 . Interestingly, only one third reported an intrinsic desire to try stopping one of their medications.…”
Section: Discussionsupporting
confidence: 91%
“…Successful deprescribing requires exploring patients' feelings about taking medication, discussing goals and treatment preferences, and addressing questions and concerns 6 . One way to explore patients' feelings about medication use is by use of the revised Patients' Attitudes Towards Deprescribing (rPATD) questionnaire, 7 which has been widely used to explore attitudes across patient populations 8‐11 . However, while the majority of previous studies concern older people in general, only few studies assess the attitudes of older people with frailty and/or limited life expectancy 12 for whom deprescribing is particularly relevant.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in line with previous research. Another study conducted in Switzerland found that 77% of older adults would be willing to stop one or more of their medications [39] and similar proportions were found in studies in other countries (88% in Australia [47], 92% in the United States [50], 83% in Singapore [51]). While these numbers have to be interpreted with caution (e.g.…”
Section: Characteristicssupporting
confidence: 65%
“…One study presented factor scores on a scale up to 100 (10), which we divided by 20 to represent the original scale up to 5. For one study that presented "inappropriateness" without carrying out the inverse scoring (11), we reversed the scores and reported associations. We tested for differences at study level in (a) willingness to stop medication, (b) satisfaction with medication, and (c) the four rPATD factors using ANOVA, comparing global regions (USA, Europe, Australia, Asia, Africa), high-income versus lowmiddle-income countries (OECD classification), and healthcare settings (primary care, outpatient, inpatient, nursing home).…”
Section: Methodsmentioning
confidence: 99%